2014
DOI: 10.1016/j.quascirev.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Continuing upward trend in Mt Read Huon pine ring widths – Temperature or divergence?

Abstract: a b s t r a c tTo date, no attempt has been made to assess the presence or otherwise of the "Divergence Problem" (DP) in existing multi-millennial Southern Hemisphere tree-ring chronologies. We have updated the iconic Mt Read Huon pine chronology from Tasmania, southeastern Australia, to now include the warmest decade on record, AD 2000e2010, and used the Kalman Filter (KF) to examine it for signs of divergence against four different temperature series available for the region. Ring-width growth for the past t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 96 publications
(149 reference statements)
1
9
0
Order By: Relevance
“…Analogous to our findings, dendroclimatic research at high elevations in Tasmanian temperate rain forest in SE Australia has identified time‐dependent growth‐climate relationships over the past 100 years, as well as an unprecedented increase in growth over the past two decades (Allen et al., ). This area in Tasmania shares similar climatic conditions (i.e.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Analogous to our findings, dendroclimatic research at high elevations in Tasmanian temperate rain forest in SE Australia has identified time‐dependent growth‐climate relationships over the past 100 years, as well as an unprecedented increase in growth over the past two decades (Allen et al., ). This area in Tasmania shares similar climatic conditions (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…This area in Tasmania shares similar climatic conditions (i.e. high rainfall, cool conditions, and overall mild seasonality) with western SSA (Allen et al., ; Garreaud et al., ). Tree‐growth responses across rain forest to semi‐arid woodland biomes at mid‐latitudes in the Southern Hemisphere in response to the 1950s shift in climate has been linked to warming/drying trends, primarily due to shifts in the latitude and strength of the Southern Westerlies (Allen, Ogden, Buckley, Cook, & Baker, ; Allen et al., ; Villalba et al., ).…”
Section: Discussionmentioning
confidence: 92%
“…Growing seasons in the temperate belt of the Southern Hemisphere have become warmer and drier as the midlatitude westerly flow has weakened during recent decades (Gillett et al, 2006;Garreaud et al, 2009). Warming has stimulated tree growth in cool and moist subalpine forests of Tasmania and New Zealand (Allen et al, 2014(Allen et al, , 2001Cook et al, 2000;Villalba et al, 2012) whilst drying has reduced growth rates in mesic and dry forests of southern South America (Christie et al, 2011;Mundo et al, 2012;Villalba et al, 2012). Temporal stability of significant correlations between tree-ring chronologies and climatic variables suggest that forests growing at marginal locations, where growth is dominantly limited by either temperature or moisture, have responded consistently to this observed shift in growing season climate Muñoz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Palaeoendemic species are eliminated by moderate to severe fire events and poorly regenerate after low‐intensity fires by seed or asexual growth (Kirkpatrick, ). Many of these species are long‐lived enabling reconstruction of past climate variation (Allen et al ., ,b) and dating of past fire events using fire scars (Holz et al ., ). The region also has numerous fossil pollen records that have enabled an understanding of the distributional changes of plant species in response to environmental change since deglaciation, and in some cases, the LGM (Colhoun & Shimeld, ).…”
Section: Introductionmentioning
confidence: 97%
“…After European settlement in the early 19th century, there has been an increase in anthropogenic ignitions exacerbated by periods of lower than average rainfall resulting in substantial contraction of fire‐sensitive vegetation (Mariani & Fletcher, ). Since the end of the 20th century, more frequent and longer durations of droughts coupled with increased dry lightning storms (Allen et al ., ,b) has led to more landscape fires (Parks and Wildlife Service ). Collectively, these factors have resulted in the loss of c .…”
Section: Introductionmentioning
confidence: 99%